2019
DOI: 10.1021/acscatal.9b03514
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Ruthenium-Based Multifunctional Electrocatalyst

Abstract: A high-efficiency trifunctional electrocatalyst is required for practical applications of regenerative fuel cells, because the hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), and oxygen evolution reaction (OER) are their core electrode reactions. However, implementation of both hydrogen and oxygen electrodes is hindered by low activity and poor stability of electrocatalysts for both water splitting and oxygen reduction. Herein, we report a high-temperature annealing strategy to fabricate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 39 publications
1
73
0
Order By: Relevance
“…Meanwhile, the Ru loading of the Ru-SA/Ti 3 C 2 T x catalyst after 32 h electrolysis is determined to be 0.21 wt%, further confirming its rigorous stability. This finding can be ascribed to the strong interaction between Ru SAs and Ti 3 C 2 MXene support, [28,30] which is beneficial to stabilize the Ru SAs during electrolysis.…”
Section: Oer Performance In Acidic Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the Ru loading of the Ru-SA/Ti 3 C 2 T x catalyst after 32 h electrolysis is determined to be 0.21 wt%, further confirming its rigorous stability. This finding can be ascribed to the strong interaction between Ru SAs and Ti 3 C 2 MXene support, [28,30] which is beneficial to stabilize the Ru SAs during electrolysis.…”
Section: Oer Performance In Acidic Mediamentioning
confidence: 99%
“…Until recently, only one study has confirmed that single-atomic Ru-N 4 sites can simultaneously catalyze HER, ORR, and OER. [30] However, trifunctional activities for these isolated Ru-N 4 sites in an acidic system still need to be improved for practical acidic electrolysis, and studies on this issue also are extremely limited. Previous studies have reported that the coordination effect of active sites can considerably affect their electronic structures, subsequently tuning their electrocatalytic activity.…”
mentioning
confidence: 99%
“…Atomically dispersed metal catalysts (ADMCs) have recently emerged as a new frontier in catalysis science and have attracted extensive research attention. [ 85–88 ] Traditional heterogeneous catalysts with a broad size distribution of metal particles suffer from a low metal utilization efficiency and poor selectivity. Homogeneous catalysts with well‐defined active sites and tunable coordination environments exhibit excellent activity and exclusive selectivity for a specific reaction.…”
Section: Defect Chemistry Of Bifunctional Electrocatalystmentioning
confidence: 99%
“…[18][19][20][21] In particular, rutheniumbased (Ru-based) electrocatalysts are believed to have the great potential to replace commercial Pt/C in HER process because of its highly active performance and lower cost compared to metal Pt. [22,23] Moreover, the effective design of highly active catalysts mainly includes the regulation of component and morphology, size control, the changing of electronic structure for active sites, and so on. At present, different shaped Ru-based catalysts, such as 0D nanoparticles, 1D nanowires (NWs), and 2D nanosheets, were reported to show excellent activity for water splitting.…”
Section: Introductionmentioning
confidence: 99%